Insulin Signaling in the Peripheral and Central Nervous System Regulates Female Sexual Receptivity during Starvation in Drosophila - Lebreton, Sébastien; Carlsson, Mikael A.; Witzgall, Peter (Frontiers in Physiology, 2017)
Many animals adjust their reproductive behaviour according to nutritional state and food availability. Drosophila females for instance decrease their sexual receptivity following starvation. Insulin signalling, which regulates many aspects of insect physiology and behaviour, also affects reproduction in females. We show that insulin signalling is involved in the starvation-induced reduction in female receptivity. More specifically, females mutant for the insulin-like peptide 5 (dilp5) were less affected by starvation compared to the other dilp mutants and wild-type flies. Knocking-down the insulin receptor, either in all fruitless-positive neurons or a subset of these neurons dedicated to the perception of a male aphrodisiac pheromone, decreased the effect of starvation on female receptivity. Disrupting insulin signalling in some parts of the brain, including the mushroom bodies even abolished the effect of starvation. In addition, we identified fruitless-positive neurons in the dorso-lateral protocerebrum and in the mushroom bodies co-expressing the insulin receptor. Together, our results suggest that the interaction of insulin peptides determines the tuning of female sexual behaviour, either by acting on pheromone perception or directly in the central nervous system.